Pengaruh Disiplin terhadap Produktivitas Kerja Karyawan Bagian Produksi pada PT. Sumbertama Nusa Pertiwi BSP Unit Jambi - Meri Ardiyanti (Universitas Batanghari Jambi, 2019)
This research above to know and analize whether the discipline and work productivity at PT. Sumbertama Nusa Pertiwi is good, to know and analize of discipline to work productivity of employees at PT. Sumbertama Nusa Pertiwi.This study includes a descriptive study to test the hypotesis, sampel this study were employees PT. Sumbertama Nusa Pertiwi of 34 People, with a population census method as respondents in answering the questionnaire. The technique of colleting data using questionaires. Data analisys technique used was SPSS with simple regresi analisys and t test.The influene of despline on employee productivity production at PT. Sumbertama Nusa Pertiwi is Y = 14,919 + 0,547 X, constant of 14,919 means that if a variable is constant discpline, the labor productivity in PT. Sumbertama Nusa Pertiwi will descrease 14,919. Discpline variabel coefficient of 0,547 means that if a variable discipline increased by 1% the productivity of labor in PT. Sumbertama Nusa Pertiwi to increase by 0,547%.Based on the t test it’s known that discipline has a signnificant positive effect on employee work productivity.